2016
DOI: 10.1016/j.ejpal.2015.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Generalists versus specialists: Toward a typology of batterers in prison

Abstract: a b s t r a c tIn this study we apply the versatile/specialist offender debate to the research of intimate partner violence. We propose the existence of two types of imprisoned male batterers: the generalist and the specialist batterer. The individual, family, and community characteristics of these types of batterers are further explored in 110 imprisoned males in the Penitentiary of Villabona (Spain). As for the individual characteristics, results indicate that the generalist batterer present higher levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(90 citation statements)
references
References 60 publications
10
77
1
2
Order By: Relevance
“…Although Theobald et al (2015) did not confirm the hypothesis about the specialist batterer with higher affective traits than the generalist batterer, it is possible that the erroneous psychopathy measurement by Theobald et al (2015), conducted without the face-to-face interview, has underestimated affective psychopathic traits. Thus, further batterer typology studies based on generalization of violence, as in Herrero, Torres, Fernández-Suárez, and Rodríguez-Díaz (2016) or Theobald et al (2015), are recommended. Finally, although psychopathy was able to detect the most frequent batterer subtype, psychopathy did not differ between batterer typologies based on severity of IPV perpetration among both non-convicted (Babcock et al, 2005) and convicted samples (Echeburúa & Fernández-Montalvo, 2007;Fernández-Montalvo & Echeburúa, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although Theobald et al (2015) did not confirm the hypothesis about the specialist batterer with higher affective traits than the generalist batterer, it is possible that the erroneous psychopathy measurement by Theobald et al (2015), conducted without the face-to-face interview, has underestimated affective psychopathic traits. Thus, further batterer typology studies based on generalization of violence, as in Herrero, Torres, Fernández-Suárez, and Rodríguez-Díaz (2016) or Theobald et al (2015), are recommended. Finally, although psychopathy was able to detect the most frequent batterer subtype, psychopathy did not differ between batterer typologies based on severity of IPV perpetration among both non-convicted (Babcock et al, 2005) and convicted samples (Echeburúa & Fernández-Montalvo, 2007;Fernández-Montalvo & Echeburúa, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study school dropout was examined from a multidimensional approach, where individual, family and school (Andrei et al, 2012; Bjerk, 2012; Fortin et al, 2013; Korhonen et al, 2014) correlates of school dropout were analyzed among juvenile offenders, a population with a high risk of school dropout (Lochner and Moretti, 2004; Dianda, 2008; Ou and Reinolds, 2010; Andrei et al, 2012; De Witte et al, 2013; Korhonen et al, 2014; Einat and Einat, 2015; Lucero et al, 2015; Herrero et al, 2016; Jaggers et al, 2016). The official records of 264 juvenile delinquents were used to analyze the individual, family, and school correlates of school dropout.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Dianda (2008) found that 41% of inmates in state and federal prisons in the United States had less than a high school education, indicating that inmates who were dropouts were more likely to have served a prior sentence in prison and were more likely to have been sentenced when they were young. Similarly, Herrero et al (2016), in a sample of 110 imprisoned males in Spain, found that most of them (60%) did not have secondary studies. Likewise, Einat and Einat (2015), in a sample of 89 adult inmates in Israel, found that those who dropped out of school early began their criminal activity at an earlier stage, suggesting that completing high school reduces the probability of incarceration (Lochner and Moretti, 2004).…”
Section: Introductionmentioning
confidence: 85%
“…As Herrero, Torres, Fernández-Suárez, & Rodríguez-Díaz (2016) have recently suggested, however, the fact that severe IPV against women is overrepresented in penitentiary-based samples of male batterers might lead to a lack of representativeness of the less violent batterer. To overcome this limitation, they proposed a typology that incorporates male batterers' criminal history and identified two types of convicted male batterers: generalist and specialist batterers.…”
Section: Batterers In Prisonmentioning
confidence: 99%